70.1k views
13 votes
2/5 g+3h -6 when g=10 h=6

1 Answer

9 votes

hello!

let's evaluate this expression


\pmb{\displaystyle(2)/(5)g+3h-6 }


\pmb{\displaystyle(2)/(5) *10+3(6)-6}


\pmb{\displaystyle(2)/(5) *10+18-6}


\pmb{\displaystyle(2)/(5) *10+12}

Multiply:


\pmb{\displaystyle(2)/(5) *(10)/(1) =(20)/(5) =4}

Final Step:-


\pmb{4+12}


\pmb{16}

======================================================

note:-

Hope everything is clear; if you need any explanation/clarification, kindly let me know, and I'll comment and/or edit my answer :)

User Viilpe
by
5.5k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.